The Truro cordwainers' play: a "new" 18th century Christmas play - Millington, Peter (Routledge Journals; Taylor & Francis Ltd, 2003)
The Christmas play hitherto attributed to Mylor has been re-ascribed to Truro in the late 1780s, using biographical information concerning the actors, and physical characteristics of the manuscript. It becomes the oldest Saint George play to feature Father Christmas and the Turkish Knight, and has textual parallels with Irish folk plays.